Manuscript preservation strategy - HELILOU, Nabil (Social Sciences Journal)
The manuscript represents a key element of the memory of individuals, peoples and nations, lies not important historical memory, but also because of its association dimensions of patriotism, nationalism, and representation of the past of the nation and its present, it connects lectured the nation its past for the future will be based on the present and connected to the past of a prosperous, which contributes to the latter to continue generations and out of this importance, which is no different where two came this article to illustrate a range of strategies that will keep the manuscript, especially since it faces a wave of challenges damage and loss ......Etc